Parody Iklan, Meningkatkan Brand Awaraness melalui Olokan - Ayu, Aulia Suminar (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractÂ Usually, parody were used to show how audience dislike or resistance with certain texts. Recently, parody about the standarized herbal product , â€œMastinâ€ were circulating around social media world. This phenomenon starts from Mastin parody video on youtube. Repetitive use of Mastin' TVC lyrics, â€œkabar gembira untuk kita semuaâ€ was becoming new joke trend and slang on cyber and real world. On the other side, that was insulting and making people bored of that kind of joke. Either do Mastin, along with this trend, Mastin changes their TVC Jingle chord (until) three times in order to make audience didn't get drown on boredom. This text would be explained by reception analysis as methodology with Elaboration Likelihood Modes and Hirearchy of Effect Model as theoritical background. Subject of this research are people who reviewing Mastin on their webblog, and Mastin user that researcher met on real world.Â This study aimed to understand how audiences interpret Mastin related with this parody.Â Keyword: Parody, Mastin, Audience Reception Analysis, Elaboration Likelihood Model, Hirearchy of Effect Model